GENOMIC DIVERSITY OF NON-TOXIGENIC VIBRIO CHOLERAE EL TOR STRAINS AND METHOD FOR DIFFERENTIATION OF CHOLERA VIBRIOS WITH DIFFERENT EPIDEMIC SIGNIFICANCE, USING PCR - E. Yu. Agafonova (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
.